Thermal stability of perovskite phase in heavily Mn-doped SrTiO3 nanoparticles in oxidizing and reducing atmospheres. (15th April 2016) - Makarova, Marina V.; Artemenko, Anna; Kopecek, Jaromir; Laufek, Frantisek; Zemenova, Petra; Trepakov, Vladimir A.; Dejneka, Alexandr
Abstract: Complex investigations of the thermal stability as well as Mn-dopant distribution depending on chemical composition and processing condition have been performed in heavily doped SrTi1-x Mnx O3 nanoparticles with x = 0.2 and 0.4. Prepared nanopowders reveal stable enough cubic perovskite structure even after treatment in oxidizing atmosphere up to 1000 °C. At the same time treatment in reducing atmosphere leads to decrease of the Mn solubility limit. Mn distribution evidences a weak tendency of Mn ions to migrate to surface. This migration increases in air and decreases at treatment in oxygen atmosphere. Graphical abstract: